Does it take three to tango? An unsuspected multimorbidity of CD8(+) T cell lymphoproliferative disorder, malaria, and EBV infection - Ekemen, Suheyla; Uzay, Ant; Bassullu, Nuray; Dikicioglu-Cetin, Emel; Matsuda, Kyoko; Ince, Umit; Coban, Cevayir (BMC, 2018)
Background: Malaria is known to cause acute and deadly complications. However, malaria can cause unforeseen pathologies due to its chronicity. It increases the risk of endemic Burkitt Lymphoma development by inducing DNA damage in germinal centre (GC) B cells, and leading higher frequency of Epstein-Barr virus (EBV)-infected cells in GCs. EBV is well known for its tropism for B cells. However, less is known about EBV's interaction with T cells and its association with T cell lymphoma. Case presentation: A 43-year-old Sudanese male admitted to hospital in Istanbul, Turkey, a non-endemic country, with hyperpigmented painful skin rashes on his whole body. A complete blood count and a peripheral blood smear during admission revealed large granular lymphocytes (LGLs) with abnormally higher CD8 T cell numbers. Additional skin biopsy and pathology results were compatible with CD8(+) T cell lymphoproliferative disorder with skin involvement. Patient was treated and discharged. However, a pathologist noticed unusual structures in skin tissue samples. Careful evaluation of skin biopsy samples by polarized microscopy revealed birefringent crystalloid structures resembling malarial haemozoin mainly loaded in macrophages and giant histiocytes. After purification of DNA from the skin biopsy samples, nested PCR was performed for the detection of Plasmodium parasites and Plasmodium falciparum DNA was amplified. Because, the co-presence of EBV infection with malaria is a well-known aetiology of lymphoma, EBV-early RNA (EBER) transcripts were investigated in paraffin-embedded tissue samples and found to be positive in macrophage-like histiocytes. Conclusions: This is a unique case of malaria and EBV infection in a T-LGL lymphoma patient who presented in a non-endemic country. This case emphasizes the clinical importance of EBV monitoring in T-LGL patients with skin involvement. Notably, Plasmodium infection should be examined in patients from malaria endemic regions by pathological and molecular investigations.
Keywords: CD8(+) T-cell lymphoproliferative disorder; Cutaneous lesions; Hemozoin crystals; Epstein-Barr virus (EBV); Plasmodium falciparum malaria